Hybrid catalysts containing Ba, Ti, Mn, Na, and W for the low-temperature oxidative coupling of methane - Do, Lien Thi; Choi, Jae-Wook; Suh, Dong Jin; Yoo, Chun-Jae; Lee, Hyunjoo; Ha, Jeong-Myeong (Elsevier BV, 2021)
The oxidative coupling of methane (OCM) using hybrid catalysts containing BaTiO3 perovskite and Mn-Na2WO4 exhibited high activity and high selectivity at low temperature: 66.3 % C2+ (olefins and paraffins) selectivity and 25.9 % C2+ yield at 700 degrees C which is 100 degrees C lower than that used for Mn-Na2WO4 catalysts (800 degrees C). Upon the preparation of complex catalysts, the insertion of Mn into BaTiO3 (BaTi(Mn)O-3) and the formation of NaxMn(Ti) O-2 improved the oxygen-supplying ability of the catalysts. Additionally, strong interactions between the WO(4)(2-)anions and BaTi(Mn)O-3 or NaxMn(Ti)O-2 stabilized the WO42- anions on the surface and improved the methane activation ability of the catalysts for the favorable production of hydrocarbons. The nanoscopic modification of catalysts was confirmed using H-2-temperature-programmed reduction, transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectroscopy results.